KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE DISKURSUS MULTI REPRESENTASI DAN RECIPROCAL LEARNING - Tiagita Tristiyanti; Ekasatya Aldila Afriansyah (Universitas Muhammadiyah Ponorogo, 2017)
This research aims to determine whether there are differences in the increase in mathematical problem solving ability of students who get a cooperative learning model Diskursus Multi Representasi (DMR) and Reciprocal Learning types. This study was conducted in one of the Junior High School in Garut on pyramid and prism material. The population in the study were students of class VIII, and as many as two classes selected sample. The instrument used is test description of mathematical problem solving ability. This test instrument tests on another class who have studied the material pyramid and prism, the instrument is deemed to have qualified validity, reliability, distinguishing features, and level of difficulty. Data analysis was performed with data normality test, homogeneity test, t test, and test to determine the normalized gain increased ability students' mathematical understanding. From the results of the data analysis performed in this study can be concluded that there are no differences in the ability of solving mathematical students between experimental class one that uses a learning model Diskursus Multi Representasi (DMR) and experimental class two were using model Reciprocal Learning, which increase the ability of mathematical understanding of students from each class experimental group was included in the criteria Keywords: Mathematical Problem Solving, Discourse Multy Representation, Reciprocal Learning